Trans-Fats Inhibit Autophagy Induced by Saturated Fatty Acids - Allan Sauvat; Guo Chen; Kevin Müller; Mingming Tong; Fanny Aprahamian; Sylvère Durand; Giulia Cerrato; Lucillia Bezu; Marion Leduc; Joakim Franz; Patrick Rockenfeller; Junichi Sadoshima; et al. (EBioMedicine, 2018)
Depending on the length of their carbon backbone and their saturation status, natural fatty acids have rather distinct biological effects. Thus, longevity of model organisms is increased by extra supply of the most abundant natural cis-unsaturated fatty acid, oleic acid, but not by that of the most abundant saturated fatty acid, palmitic acid. Here, we systematically compared the capacity of different saturated, cis-unsaturated and alien (industrial or ruminant) trans-unsaturated fatty acids to provoke cellular stress in vitro, on cultured human cells expressing a battery of distinct biosensors that detect signs of autophagy, Golgi stress and the unfolded protein response. In contrast to cis-unsaturated fatty acids, trans-unsaturated fatty acids failed to stimulate signs of autophagy including the formation of GFP-LC3B-positive puncta, production of phosphatidylinositol-3-phosphate, and activation of the transcription factor TFEB. When combined effects were assessed, several trans-unsaturated fatty acids including elaidic acid (the trans-isomer of oleate), linoelaidic acid, trans-vaccenic acid and palmitelaidic acid, were highly efficient in suppressing autophagy and endoplasmic reticulum stress induced by palmitic, but not by oleic acid. Elaidic acid also inhibited autophagy induction by palmitic acid in vivo, in mouse livers and hearts. We conclude that the well-established, though mechanistically enigmatic toxicity of trans-unsaturated fatty acids may reside in their capacity to abolish cytoprotective stress responses induced by saturated fatty acids. Keywords: Fasting, Ketogenic diet, Immune response, Immunosurveillance, Obesity, Aging, Cytoprotection, Systems biology